Equações de valores previstos de pico de fluxo expiratório em diferentes equipamentos de uma amostra da população brasileira - Ike, Daniela (Universidade Federal de São Carlos, 2015)
The peak expiratory flow (PEF) is a simple and objective method that evaluates primarily the proximal airways caliber. The ease of handling and low cost of portable PEF meters have become its frequent use, however few studies have analyzed the agreement of the obtained values in different equipment, as well as compared its reference values, which justifies the Study I, which had as its objective to compare the obtained values, analyze the agreement of three portable PEF meters and check if the reference values that accompany these devices are appropriate for the population studied. 168 healthy individuals were evaluated, of both genders, in the age group of 20 to 80 years, who underwent PEF measurements in Mini-Wright®, Assess® and Air Zone® meters; then, the obtained values were compared to predict proposed by Leiner et al. (1963) and Nunn and Gregg (1989). The statistical analysis was performed using the Kolmogorov-Smirnov test, ANOVA, Wilcoxon test, Spearman's correlation test and Bland-Altman s agreement test, with a significance level of 5%. Significant differences were found in the PEF obtained values between Mini-Wright® and Assess® meters in both genders, between the Air Zone® and Assess® meters only in men, and between Mini-Wright® and Air Zone® meters only in women; and the PEF predict values in the three devices were considered significantly higher than those obtained in both genders. Moderate significant correlations were found between the obtained and predict values in men and women, but there was no agreement between the PEF obtained values in the meters, due to the great variation in the limits of agreement and large interindividual variation. It was concluded that the obtained values in the three meters are not interchangeable and the predicted values overestimated the obtained, indicating its inconsistency for the sample studied, that stimulated the realization of Study II, which aimed to establish PEF reference values for adults and elderly from Southeast region of Brazil based on the obtained values of three portable meters: Mini-Wright®, Assess® and Air Zone®. 373 healthy individuals were evaluated, of both genders, aged 20 to 80 years, who underwent PEF measurements in Mini-Wright®, Assess® and Air Zone® meters. The statistical analysis was performed by multiple linear regression analysis by stepwise selection method to determine the explicative variables and were tested three different models: using variable unit, logarithmic and adjust by age; and then the paired t-test was applied to compare the obtained values with predict by new model and to check the validation of the proposed model, with a significance level of 5%. Of the models tested, adjust by age showed the best agreement and the equations varied according to the meter and the coefficients age, corporal mass, height and body mass index (BMI) explained more than 90% variation in PEF. In the comparison of obtained values with those proposed by new model, no significant difference was found, confirming the validation of equations proposed in the meters. Therefore, equations of PEF were established for adults and elderly from Southeast region of Brazil, separated by gender and for each meter evaluated: Mini-Wright®, Assess® and Air Zone® considering the inadequacy of the common use of an equation for the three meters used. These equations enable the correct interpretation of PEF values in clinical practice.
Keywords: Fisioterapia respiratória; Pico do fluxo expiratório; Valores de referência; Testes funcionais dos pulmões; Peak expiratory flow rate; Reference values; Respiratory function tests; Physical therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL